The COVID-19 impact crisis communication model using gending jawa local wisdom - Puji Lestari; Sularso Sularso (International Journal of Communication and Society, 2020)
Pandemic COVID-19 is a new epidemic that is sweeping the world with a high level of fatal potential. The role of communication is vital as a response to global health disasters. Thus, the communication network and information dissemination process about COVID-19 need to be expanded as a disaster mitigation effort. The question is how information dissemination can be done, whereas, on the other hand, a person is prohibited from crowding and having physical meetings. Based on this question, this research was conducted to obtain a crisis communication model and what strategies are used in communicating it. This study aims to find a COVID-19 impact crisis communication model using the local wisdom of Gending Jawa in Ngandong Village.  Gending Jawa is Javanese traditional music, also known as Karawitan. This study used a qualitative descriptive method with a simulation with the leaders and members of the Jati Art Studio, community leaders/religious leaders, and village officials. The results of this study are in the form of the discovery of a COVID-19 impact crisis communication model using the local wisdom of Gending Jawa. The contribution of this research is the COVID-19 crisis communication, model whose results can be used or applied to other communities.